(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Current methods for determining target IOP have disadvantages. Investigation of data on corneoscleral rigidity and corneal thickness in patients with stabilized primary open-angle glaucoma of stages I-II may improve the method of determining target IOP. Purpose. To study the correlation between indices of corneoscleral rigidity, corneal thickness and target IOP in patients with stabilized primary open-angle glaucoma (POAG) of stages I-II. Material and Methods. 30 patients (30 eyes) with stabilized POAG of the І-ІІ stage were examined. The patients underwent pachymetry, applanation tonometry, dynamic contour tonometry, corneal rigidity determination and tonography. The progression of glaucoma was monitored by the HFA II Central 30-2 Threshold Test and SOCT Copernicus + units. Target IOP was calculated taking into account the age and the level of diastolic blood pressure. Results. It was found that, in group 1 with target IOP of 6.2 -13.9 mm Hg, the corneal thickness was 540-590 μm and rigidity of the cornea ranged from 1.0 to 4.0 mm Hg; while in group 2 with target IOP of 14.0 -16.8 mm Hg, the corneal thickness was 510-570 μm and rigidity of the cornea ranged from -3.0 to 1.5 mm Hg. Conclusions. It was found that the lower a value of achieved target IOP, the higher corneal rigidity in patients with stabilized stage I-II POAG.